Experiencing less apprehension and engaging religious communication: the team-based project learning practices - Yusuf Hanafi; Muhammad Saefi; M. Alifudin Ikhsan; Tsania Nur Diyana; Nur Faizin; Abd Basid; M. Rizal Ramadhan (Cogent Education, 2024)
AbstractThis pre-experimental study aims to explore the efficacy of the Team-based Project (TBP) as a pedagogical approach to enhancing the acquisition of religious communication skills. The TBP was incorporated into a religious education module, addressing pivotal religious inclusivity and moderation themes amongst undergraduate cohorts. Participants were 288 students who participated in a TPB program. Our attention is drawn to the students’ deliberations on TPB activities during the preliminary phase and the initiation, groundwork, execution, and culmination of presenting the project via video. Two salient aspects of the educational outcomes emerged. Firstly, the TBP model proved instrumental in fostering elevated religious communication proficiencies amongst students. Secondly, there was a notable decline in communication apprehension attributable to students’ religious discourse. Such outcomes are intrinsically linked to the TBP's foundational elements of collaboration and dialogue. Furthermore, this investigation underscores the advantages and challenges inherent in employing video-based technological platforms as contemporary pedagogical instruments. Within the scope of this research, we delineate the protocols requisite for the TBP's methodologies to evaluate student accomplishments through an array of formative and summative assessments.